EMPLOYEE PERFORMANCE BASED ON LEADERSHIP STYLE, JOB PROMOTION AND WORK ENVIRONMENT - Khayatun, Siti; Hartarini, Yovita Mumpuni; Ariyanti, Lisa (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
This study aims to determine the direct or indirect effects of performance issues in a service company, namely